ANALYSIS OF USER SATISFACTION LIBRARY ONLINE CATALOG AT UPN VETERAN EAST JAVA USING EUCS METHOD - Khansa Renata; Arista Pratama; Anita Wulansari (Jurnal Teknologi Informasi Universitas Lambung Mangkurat (JTIULM), 2022)
The development of information technology in this digital era has prompted numerous changes in many aspects of life, notably in the field of libraries, that are necessary to satisfy the demands of librarians to locate information easily, quickly, and precisely. OPAC (Online Public Access Catalog), often known as Online Catalog, is a website-based catalogue system used to search for information on library materials so they may be accessible whenever and wherever. One of the academic libraries that have used the Online Catalog is Universitas Pembangunan Nasional "Veteran" East Java. The purpose of this study is to determine what factors influence online catalogue user satisfaction using the End-User Computing Satisfaction (EUCS) model approach with two additional independent variables, System Speed and System Reliability. End-User Computing Satisfaction is one of the methods used to evaluate the overall system for user satisfaction. Proportional stratified random sampling was employed as the sample collecting method in this study, with a total of 303 respondents. The research data obtained from the questionnaire results were processed using SmartPLS 3.2.9 software. Based on the results obtained, accuracy, format, and ease of use are the three factors that have a positive and significant effect. In addition, the most influencing factor for Online Catalog user satisfaction is the format.